Peran Filsafat Ilmu Dalam Proses Pembelajaran Siswa Sekolah Dasar Kelas Tinggi di SDN Bulakan 1 Kecamatan Cibeber - Herlina, Ane; Silalahi, Suandi (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
This study aims to examine the role of philosophy of science in the learning process of students at SDN Bulakan I. Philosophy of science has a major contribution in developing students' critical and analytical thinking skills. Through a qualitative approach with a case study at SD Bulakan 1, data were collected through observation and interviews with teachers and students. The results of the study indicate that the application of philosophy of science in learning can improve students' critical and analytical thinking skills, as well as increase curiosity and motivation to learn. Learning is integrated with discussion, reflection, and problem solving, which encourages students to be more actively involved. Teachers reported increased student engagement and their ability to connect abstract concepts with everyday life.Overall ,philosophy of science has been shown to have apositive impact on students'cognitive deelopment and thequality of learning at SD Bulakan 1.